2002
DOI: 10.1097/00003246-200206000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Selective decontamination of the digestive tract to prevent postoperative infection: A randomized placebo-controlled trial in liver transplant patients

Abstract: Selective decontamination of the digestive tract does not prevent infection in patients undergoing elective liver transplantation and increases the cost of their care. It does, however, affect the type of infection. Infections with Gram-negative bacilli and with Candida species are replaced by infections with Gram-positive cocci.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
46
0
2

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(51 citation statements)
references
References 21 publications
3
46
0
2
Order By: Relevance
“…Although 1 study suggested that SID could reduce the relative incidence of infections by enteric bacteria in comparison with a historical cohort, 16 no effect on the global incidence of infection or the mortality could be demonstrated in a randomized study. 17 It is important to note that in this last study, fluoroquinolones were administered not after transplantation but while patients were on the waiting list. Although FQ-SID appeared to reduce the incidence of infections due to enteric bacteria in LTRs, this effect was not evident after adjustments by other variables, including the transplant center.…”
Section: Discussionmentioning
confidence: 95%
“…Although 1 study suggested that SID could reduce the relative incidence of infections by enteric bacteria in comparison with a historical cohort, 16 no effect on the global incidence of infection or the mortality could be demonstrated in a randomized study. 17 It is important to note that in this last study, fluoroquinolones were administered not after transplantation but while patients were on the waiting list. Although FQ-SID appeared to reduce the incidence of infections due to enteric bacteria in LTRs, this effect was not evident after adjustments by other variables, including the transplant center.…”
Section: Discussionmentioning
confidence: 95%
“…Most studies showed that SBD was indeed able to reduce bacterial colonization of the gut, but had no impact on overall infection rates or mortality. The spectrum of isolated bacteria under SBD changed from Gram-negative to Gram-positive bacteria, especially Enterococci [23,24].…”
Section: Preventionmentioning
confidence: 99%
“…Patients undergoing liver transplant are very vulnerable to infection during the early post-operative period, particularly with gram-negative organisms. SDD has been studied in these patients in several RCTs [111][112][113] and meta-analyses [114]. The results have been conflicting and several small RCTs failed to show any benefit of SDD over standard care following liver transplant.…”
Section: Evidence Supporting Use In Surgical Patientsmentioning
confidence: 99%